The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/fwb.13875
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal diversity of aquatic plants in the Qinghai‐Tibet Plateau

Abstract: Altitudinal diversity of terrestrial plants has been widely studied, whereas little is known for the patterns of aquatic plants. Here, we used a standardised field dataset to quantify the altitudinal patterns in the diversity and structure of aquatic plant assemblages, as well as the relationships between diversity indices and environmental variables. Large‐scale field investigations were carried out in 128 sites ranging from 2,280 to 5,020 m above sea level across the southern part of Qinghai‐Tibet Plateau, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 78 publications
(116 reference statements)
6
24
0
Order By: Relevance
“…Indeed, upper canyon streams, especially those glacier‐fed ones, harbour many unique and environmentally sensitive species and lineages (Li, Wang, et al, 2019; Xu et al, 2018), as well as serve as sources of colonizers to streams in the lower reaches. These streams also have experienced and are forecasted to experience increasingly rapid climate change (Hamerlik & Jacobsen, 2012; Zhou et al, 2022). With the intensification of global warming, invertebrate assemblages in currently cold‐climate upper streams may be gradually replaced by those living in the lowland area.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, upper canyon streams, especially those glacier‐fed ones, harbour many unique and environmentally sensitive species and lineages (Li, Wang, et al, 2019; Xu et al, 2018), as well as serve as sources of colonizers to streams in the lower reaches. These streams also have experienced and are forecasted to experience increasingly rapid climate change (Hamerlik & Jacobsen, 2012; Zhou et al, 2022). With the intensification of global warming, invertebrate assemblages in currently cold‐climate upper streams may be gradually replaced by those living in the lowland area.…”
Section: Discussionmentioning
confidence: 99%
“…environmental filtering) is most often the predominant force of community assembly (Heino, Melo, Siqueira, Soininen, et al, 2015; Hill et al, 2019). However, it is still unclear whether these findings and rules are applicable to aquatic communities in alpine regions, such as the Tibetan plateau (also known as the ‘World's Third Pole’), where related research is still in its infancy (Zhou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A hump‐shaped pattern between species richness (SR) of aquatic plants and latitude was found across Europe and North Africa, with the highest peak being located between 40° and 50°N (Chappuis et al, 2012), and this pattern has been confirmed by recent work on freshwater plants in Europe, which found the highest peak at ~55°N (Alahuhta et al, 2020). Second, aquatic plant diversity commonly decreases with increasing altitude (Jones et al, 2003; Lacoul & Freedman, 2006a; Hrivnák et al, 2013; Zhou et al, 2022a), and a recent study in northern Spain found that altitude was not a good predictor of the diversity of aquatic plant assemblages across ponds ranging from 700 to 2100 m above sea level (Fernández‐Aláez et al, 2018). Third, there have been few reports on the longitude pattern of aquatic plant diversity, but the study on the local diversity pattern of aquatic plants in the Hexi Corridor of China shows that there is no significant correlation between longitude and diversity (Tian et al, 2020).…”
Section: Introductionmentioning
confidence: 99%